The anti-breast cancer property of physcion via oxidative stress-mediated mitochondrial apoptosis and immune response - Luping Zhang; Ruitao Dong; Yu Wang; Longxiang Wang; Tian Zhou; Dongxu Jia; Zhaoli Meng (Taylor & Francis Group, 2021)
Context Physcion (Phy) exerts several pharmacological effects including anti-inflammatory, antioxidant, and antitumor properties. Objective This study investigates the cytotoxicity and its underlying mechanisms of Phy on breast cancer. Materials and methods Human breast cancer cell MCF-7 was treated with 5-400 µM Phy for 24 h, MCF-7-xenografted BALB/c nude mice and immunosuppressive mice model induced by cyclophosphamide were intraperitoneally injected with 0.1 mL/mouse normal saline (control group) and 30 mg/kg Phy every other day for 14 or 28 days, and pathological examination, ELISA and western blot were employed to investigate the Phy anti-breast cancer property in vitro and in vivo. Results In MCF-7 cells, Phy 24 h treatment significantly reduced the cell viability at dose of 50-400 µM and 24 h, with an IC50 of 203.1 µM, and 200 µM Phy induced 56.9, 46.9, 36.9, and 46.9% increment on LDH and caspase-3, −8 and −9. In MCF-7-xenograft tumour nude mice and immunosuppressive mice, 30 mg/kg Phy treatment inhibited tumour growth from the 8th day, and reduced Bcl-2 and Bcl-xL >50%, HO-1 and SOD-1 > 70% in tumour tissues of immunosuppressive mice. In addition, Phy reduced nuclear factor erythroid 2-related factor 2 > 30% and its downstream proteins, and enhanced the phosphorylation of nuclear factor-kappa B > 110% and inhibitor of NF-кB α > 80% in the tumour tissues of BALB/c mice. Discussion and conclusions This research demonstrated that Phy has an anti-breast cancer property via the modulation of oxidative stress-mediated mitochondrial apoptosis and immune response, which provides a scientific basis for further research on its clinical applications.